Implementasi Algoritma Greedy Pada Pewarnaan Wilayah Kecamatan Sukodadi Lamongan - Umi Maftukhah; Siti Amiroch; Mohammad Syaiful Pradana (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2020)
Graph theory can be applied in various fields of science such as transportation problems, communication networks, operations research, chemistry, cartography and so on. Graph theory does not only represent structure but in its application, a graph can also be colored. Many problems have graph coloring characteristics such as regional coloring. This regional coloring theory was applied to the map area of ​​Sukodadi District which consists of 20 villages. In this area coloring uses the Greedy algorithm by first making a dual graph consisting of 20 vertices and 43 edges. Based on the results of regional coloring, the minimum number of colors is 4, namely red, blue, green and yellow, with each neighboring village having a different color.